THE EFFECTIVENESS OF TWO STAY TWO STRAY (TSTS) STRATEGY TOWARDS READING COMPREHENSON OF TENTH-GRADE STUDENTS AT SMA YOS SUDARSO METRO - Nurul Hidaya Tika; Dedy Subandowo; Bambang Eko Siagiyanto (Journal of English Education and Entrepreneurship (JEEP), 2025)
The Two Stay Two Stray (TSTS) cooperative learning approach aimed to improve student participation and involvement during collaborative assignments. The impact of TSTS on the reading comprehension of tenth-grade students at SMA Yos Sudarso Metro was examined in this study. Instruments for the pre-test and post-test were used in a quantitative quasi-experimental approach. Thirty-five students from the experimental class (Pratama 1) and thirty-five students from the control class (Pratama 3) made up the sample, which was selected using cluster random sampling from the population of 137 students. SPSS version 27 was used for data analysis. The results revealed that the experimental class's pre-test mean score was 45.29 (SD = 9.339), while the control class's was 57.97 (SD = 18.883). Then, the control class scored 71.17 (SD = 17.431) on the post-test, whereas the experimental class scored 69.69 (SD = 13.955). A significant value of 0.000 was identified through hypothesis testing, suggesting that TSTS influenced students' reading comprehension. Nevertheless, the second hypothesis provided a significance value of 0.695, indicating that there was no significant distinction between TSTS and conventional teaching. Overall, the study found that while TSTS improved reading comprehension, it did not significantly improve conventional approaches in this aspect.